DEVELOPMENT AND VALIDATION OF A CUSTOMIZED VOCATIONAL PROGRAM FOR ADULTS WITH MILD INTELLECTUAL DISABILITIES (Proceedings of International Conference on Special Education, 2015)
The study focused on the development and validation of a customized vocational program for adults with mild intellectual disabilities to prepare them for independent and gainful living. The program was based on basic vocational skills such as grooming, social skills, cleaning, frying, sorting, selling, money changing and washing dishes, and other related skills in physical, intellectual and socio-emotional present among the participants. It consisted of pre- referral / evaluation, orientation, workplace readiness training and job shadows of internship. This was evaluated by Special Education (SPEd) and Technological and Livelihood Education (TLE) teachers to assess the attainability of objectives, congruence of activities to objectives, adequacy of activities to objectives, appropriateness of resources and appropriateness of the success indicators. After the assessment, the customized vocational program was piloted with ten adults with mild intellectual disabilities who were aged eighteen and above. The program developed was found to be appropriate for adults with mild intellectual disabilities. Based on the findings and conclusions of this study, the researcher recommends the program be extended to all public schools with special education classes so that children with special needs, regardless of their economic status, will have the opportunity to be trained and have the chance of being independent and productive; and that the qualified adults with intellectual disabilities be given continuous upgrading to provide opportunities for professional development to build competence and instill confidence among them.